EFFECT OF FROST ON GERMPLASM USED IN RESTORATION OF DEGRADED AREA IN THE SERRA DO ITAJAÍ NATIONAL PARK - Meneghetti, Carlos; Vitorino, Marcelo Diniz (Floresta, 2018)
Frosts that occur in the Southern Brazil limit the development and survival of seedlings used for restoration projects and may cause significant losses. The objectives of this study were: evaluating the effect of frosts on seedlings produced by seeds collected around a degraded area inside the Serra do Itajaí National Park (PNSI) and used to restore this area; and validating the use of polyester printed labels for marking seedlings. Planting was carried out in adapted Anderson Groups, with 25 seedlings per module. Survival rates for frost were evaluated in 750 seedlings, identified at the species level, classified according to their ecological group, and used in three areas designated as A, B and C. 80% of the seedlings were planted in sloping area and 20%, in lowland area. For the identification of the seedlings, labels printed by a laser printer were used on matte polyester film and affixed with plastic polyamide clamps. This method proved to be practical, inexpensive and resistant to the climate action (heat, humidity and precipitation). Besides, it does not suffer attacks from the local fauna. The overall survival rate was 55.87%, whereas survival rates by ecological groups were 76.67% for shadow tolerant climax, 53.75% for light demanding climax, and 55.63% for the pioneer. The highest survival rates were the ones from seedlings located on the slopes. It was possible to verify that the local germplasm is well adapted to the frosts that occur in the region.